Performance and Emission Characteristics of Pyrolysis Oil Obtained from Neem de Oiled Cake and Waste Polystyrene in a Compression Ignition Engine - D. Raguraman; Aditya Kumar; S. Prasanna Raj Yadav; Pandurang Y. Patil; J. Samson Isaac; C. Sowmya Dhanalakshmi; P. Madhu; J. Isaac JoshuaRamesh Lalvani (Advances in Materials Science and Engineering)
Plastic is a resilient, chemically inert, lightweight, and low-cost material. It sticks around in the environment for more than hundred years, threatening nature and spreading toxins. The current study deals with the use of waste polymeric materials and de oiled cake for the production of liquid oil and its blend on the performance and emission characteristics of diesel engine. The tests were conducted in an engine fuelled with diesel and four distinct blends such as 5% (B5), 10% (B10), 15% (B15), and 20% (B20), respectively. The liquid oil was produced by co-pyrolysis of neem de oiled cake (NDC) and waste polystyrene (WPS) in 1 : 2 blend ratio. The raw pyrolysis oil and its different blends were tested for their physical and chemical characteristics in order to find their suitability. Brake power (BP), brake thermal efficiency (BTE), brake-specific fuel consumption (BSFC), emissions of carbon monoxide (CO), hydrocarbon (HC), and nitrogen oxide (NOx) are used to assess the performance of the engine. The experimental results reveal that BTE at all blends is lower than diesel at all loads and the BSFC increases with increasing blend ratio and falls with increasing engine load. At higher loads, the deviation of performance and emission values from baseline diesel up to B10 is very small. It is found from the results that the liquid oil derived from NDC and WPS up to 10% blend will be the promising additive for fossil fuels.